Bleeding Following Pediatric Liver Transplantation: A Brief Overview - Gunawan, Ferriansyah; Ramlan, Andi Ade Wijaya (Majalah Anestesia & Critical Care, 2024)
End-stage liver disease (ESLD) occasionally needs liver transplantation (LT) as a life-saving treatment. In pediatric population, LT procedure is more complicated than adults, since they are mainly caused by extrahepatic cholestasis, has a variety of age groups, and has various infection susceptibilities. Furthermore, there is a complication related to LT, such as bleeding, which cannot be disregarded because it may aggravate patients’ conditions and necessitate reoperation. Moreover, in the case of hepatic artery thrombosis and portal vein thrombosis, which is caused by severe bleeding, patients and grafts’ survival may be significantly reduced. In this review, we are discussing bleeding following LT phenomena from the basic introduction, pathophysiology, prevention, monitoring, and treatment